Engineering mechanics : statics - Bedford, Anthony. (Addison-Wesley, 1997)
Introduction; Vectors; Forces; Systems of forces and moments; Objects in equilibrium; Structures in equilibrium; Centroids and centres of mass; Moments of inertia; Distributed forces; Friction; Virtual work and potential energy.